Exploring the Evolving Landscape of Digital Library Services and Applications - Rawat, Shikha (Journal of Advanced Research in Library and Information Science, 2024)
In the rapidly advancing digital age, libraries are undergoing a profound transformation, transitioning from traditional repositories of physical books to dynamic hubs of digital information. This review delves into the multifaceted realm of digital library services and applications, analyzing the current landscape, emerging trends, challenges, and future prospects. From digitization efforts to innovative user-centric platforms, this article navigates through the diverse facets of digital libraries, shedding light on their pivotal role in shaping scholarly communication, research dissemination, and knowledge access in the 21st century. By exploring the impact of Open Access initiatives, data curation strategies, and technological advancements, this review elucidates the transformative potential of digital libraries in democratizing access to information, preserving cultural heritage, and fostering interdisciplinary collaboration. Furthermore, it examines the evolving challenges faced by digital libraries, including funding constraints, copyright issues, and the imperative to address digital equity disparities. Through a comprehensive analysis of current practices and future directions, this review offers insights into the critical role of digital libraries as catalysts for innovation, education, and societal progress.